Wind Energy : an Introduction. - El-Sharkawi, Mohamed A. (CRC Press, 2015)
Wind Energy: An Introduction covers wind energy system types, operation, modeling, analysis, integration, and control. Beginning with a history of the development of wind energy, this comprehensive book:Explains the aerodynamic theories that govern the operation of wind turbinesPresents wind energy statistics to address the stochastic nature of wind speedEmploys the statistical modeling of wind speed to evaluate sites for wind energy generationHighlights the differences between the most common types of wind turbinesAnalyzes the main power electronic circuits used in wind energyDetails the indu.